Examining the Mediating Effects of Social Capital and Community-Based Tourism on the Role of Tourism Villages in Sustainable Tourism - JUMIATI, Jumiati; SAPUTRA, Boni; FRINALDI, Aldri; PUTRI, Nora Eka (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024DO - 10.14505/jemt.v15.1(73).15, 2024)
Sustainable tourism is still a topic of study that is predicted in tourism research in Indonesia. Various strategies and efforts have been made to create sustainable tourism, starting from issuing various government policies supporting sustainable tourism programs involving the private sector and the community. However, the results achieved still need to be optimal. There are so many factors that can affect sustainable tourism. Among the variables that are stated to have a contributing influence on it, they will be discussed in this study. This study aims to analyze the mediating role of social capital and community-based tourism between the influence of tourism villages on sustainable tourism in rural tourism in West Sumatra, Indonesia. Quantitative research of the associative type is sought to reveal the hypothesis proposed. A total of 422 samples were used in this study. The research instrument in the form of a validated and highly reliable questionnaire was used, supported by literature studies and documentation. Data analysis used Structural Equation Modeling (SEM) statistics Analysis Moment of Structural (AMOS) and continued with the Sobel test. The results proved that the role of tourism village through the mediating role of social capital and community-based tourism proved to have a significant effect on sustainable tourism but not a partial effect. The role of tourism village affects social capital and community-based tourism, while social capital and community-based tourism also significantly affect sustainable tourism.